Tecnologias de informação e comunicação no contexto rural brasileiro: o modelo de monitoramento agrícola do sistema Irriga® - Viero, Verônica Crestani (2009)
The rural areas experienced rapid changes in the last three decades. Producers have had to adapt to changes in forms of production, marketing and even social relations, involving the need to adhere to technological innovations, review the management of properties and adapt to the vision of enterprise agriculture business. The changes in the processes of technology transfer to the farmer tried to follow the technological developments, especially the advancement of the Internet. However, the uptake of new technologies is not so homogeneous by farmers. Considering that this study aimed to evaluate the overall influence of a system for monitoring farm online, the IrrigaSystem, the diffusion of Information and Communication Technologies - ICTs in rural areas. With this, it was possible to answer the question: systems that provide for the use of technologies in the field, as Irriga®, actually contribute to the diffusion of ICTs in rural areas? To achieve the proposed objectives, and discuss the theoretical framework on the main concepts involved in the issue, was chosen to conduct a field research study of the type of case, with a qualitative approach. Interviews with rural producers users of the system in the states of Goiás and Rio Grande do Sul were made to obtain information. The systematic application was face to face and selection of interviewees was made for convenience. To analyze the informations was used the technique of analysis of content. Showed that the move irreversibly ICTs in rural areas, however, this progress does not occur in the same way between Brazilian regions, differing mainly by reasons of economic order. Moreover, the interviews showed that the problem of diffusion of innovations in rural areas takes place, mainly from two factors: on the ICTs point of view, it is bounded to the connection obstacles in the Brazilian rural environment, and on the rural producers‟ point of view, it is due to the digital illiteracy problem.